Transported joint probability density function simulation of turbulent spray flames combined with a spray flamelet model using a transported scalar dissipation rate - Hu, Yong; Olguín Astudillo, Hernán Andrés; Gutheil, Eva (Combustion science and technology, 2017)
Numerical simulations of a turbulent ethanol/air spray flame are performed using a combined formulation of a joint gas mixture fraction-enthalpy probability density function (PDF) and a spray flamelet model, where the scalar dissipation rate of the mixture fraction is described with a transport equation. Spray evaporation is included in the flamelet model through the pre-calculation of counterflowing laminar spray flames with a detailed reaction mechanism of 38 species and 337 elementary reactions for ethanol/air combustion. A transport equation for the mean scalar dissipation rate of the mixture fraction is derived, taking into account the spray evaporation. The computed results are compared with the experimental data provided by A. Masri, University of Sydney, Australia. All major spray flame characteristics, including the Sauter mean diameter, the droplet velocity, and its turbulent fluctuations as well as gas temperature, generally show good agreement with experiments. Different models for the scalar dissipation rate of the mixture fraction are not significantly different for the flame under consideration except for inside the chemical reaction zone, where the new model shows some improvement compared to the experiment.